THE ROLE OF CASH FLOW OF OPERATIONAL, PROFITABILITY, AND FINANCIAL LEVERAGE IN PREDICTING FINANCIAL DISTRESS ON MANUFACTURING COMPANY IN INDONESIA - Finishtya, Florentina Cindy (Jurnal Aplikasi Manajemen, 2019)
The purpose of this study is to empirically test the influence of ratio on the cash flow of operational activities, profitability, and financial leverage towards financial distress condition that may emerge in manufacturing company in Indonesia. The population of this study consist of all manufacturing companies listed in Indonesia Stock Exchange in 2016. The sampling technique used is purposive sampling method, obtaining 111 manufacturing companies as the final research samples from a total data of 124 companies that were being observed. Altman Z-score model (1968) is used to determine whether the company is experiencing financial distress. Data analysis technique used is the binary logistic regression. The result of hypothesis testing shows that operating cash flow as measured by cash flow from operational/net sales is significant towards company’s financial distress, profitability measured by ROA shows a significance towards financial distress and financial leverage measured by DER does not show any significance towards financial distress.